Islamic Law and Local Religious Interpretations in the Samin Community of Central Java - Subakir, Ahmad; Wakhidah, Nur; Nazir, Muhammad; Sholihah, Mida Mar'atus (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
The Samin community's local religion was interpreted as Islam by the village government. It led some groups of the Samin community to accept and others to reject this interpretation. The article aimed to explore the implications of Islamic law on the interpretation of local religion in the Samin community in Central Java. The research employed an empirical legal approach and ethnographic perspective. Primary data was obtained using observation, interview, and documentation techniques, which were then analysed using the theories of the rule of law, al-adah muhakamah, and thick description. The study demonstrated the impact of Islamic law on the local religion of the Samin community, particularly on groups that accept the interpretation of Islam, which affects how Islamic law is applied to them. Marriages are conducted through the Religious Affairs Office. Meanwhile, divorces are handled by the Religious Court. The acceptance of Islamic law by the Samin group has had an impact on legal certainty.